Breast Cancer Chemoprevention: A Literature Review - Rukaia Sheneeb; Yousef Hasen; Wafa ALallam; Asia Fleafla (AlQalam Journal of Medical and Applied Sciences, 2021)
Many women at increased risk of breast cancer could get benefit from preventive chemotherapy. Preventive chemotherapy options for breast cancer risk reduction have been expanded in the last few years to include both selective receptor modulators (tamoxifen and raloxifene) and retinoids. Risk factors that place women at high risk for breast cancer, as well as risk calculation models appropriate for the selection of candidates for preventive therapy, are presented, followed by a review of current chemoprevention and results of some chemoprevention trials are reviewed in the present paper. Aromatase inhibitors are not linked to the increase the risk of blood clots or even uterine cancer, as tamoxifen and raloxifene are. As aromatase inhibitors are a new type of treatments, there are not much information is yet known about long term side effects that they might cause. The systemic administration of retinoids however is frequently associated with liver toxicity and abnormalities of serum lipid profiles, which might be related to an increased risk of coronary heart disease as well as the teratogenic effect of all retinoids, which limits their use in women of child bearing potential. Published guidelines on chemoprevention for breast cancer have been updated to raise awareness and encourage discussion between both the patients and their physicians. However, even with increasing the awareness and established benefits of preventive therapy, the use of chemo preventions is still low, with physician and patient barriers identified. It is prudent that these barriers be overcome to enable high-risk women with a favorable risk-to-benefit ratio to be offered chemoprevention to reduce their likelihood of developing hormone receptor-positive breast cancer. In this review article, we aimed to highlight the update on the chemo preventive strategies in breast cancer.